Pembelajaran Berbasis Praktik Rekayasa Bioteknologi dalam Produksi Cuka Buah - Vita Purnamasari; Puguh Sujarta; Jeirel Wattilete; Mesak Wandik (Bakti Hayati: Jurnal Pengabdian Indonesia, 2025)
Practice-based learning is a pedagogical approach that emphasizes the active involvement of students through direct experience and real activities in the learning process. The objectives of this community service activity are (1) to train students' skills in engineering the fruit vinegar production process in a simple, safe, and practical manner; (2) to raise students' awareness of the use of local fruits as raw materials for value-added fermentation products. The training uses two methods, namely lecture, simulation, and practice. The community service activity was carried out on August 19, 2024, at SMA Negeri 7 Jayapura, with 40 students participating. The final result was that 75% had a good understanding of the fruit vinegar-making process, 7.5% had a very good understanding, 12.5% had a poor understanding, and 5% had a very poor understanding. This activity is able to train skills and raise awareness in the use of local fruits.